2008
DOI: 10.1007/s12253-008-9000-9
|View full text |Cite
|
Sign up to set email alerts
|

p53 and BCL-2 as Prognostic Markers in Endometrial Carcinoma

Abstract: The objective of this study was to verify the frequency of p53 and BCL-2 immunohistochemical expression in patients with endometrial carcinoma and to correlate it with histological factors (histological type, tumor grade, depth of myometrial invasion, lymph node involvement and surgical staging) and survival. Forty-eight patients with endometrial carcinoma who were submitted to primary surgical treatment were assessed. p53 and BCL-2 immunohistochemical expression was determined using paraffin blocks containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
20
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 32 publications
13
20
1
2
Order By: Relevance
“…Among them, partial genes have been previously reported to be associated with EC prognosis, such as TP53 23, 24, PIK3CA 25, CDKN2A 26, 27, and PTEN 17. By performing KEGG enrichment analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, partial genes have been previously reported to be associated with EC prognosis, such as TP53 23, 24, PIK3CA 25, CDKN2A 26, 27, and PTEN 17. By performing KEGG enrichment analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They are aggressive and occur in a distinct biological environment. Gene mutation and P53 protein accumulation are often found in type II lesions [10,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one in three endometrial cancers have abnormalities of P53 by immunohistochemistry [7,[14][15][16][17]. A number of studies have shown that both P53 overexpression and mutation are associated with poor prognosis [9,10,14,15,17]. It is worth noting that earlier grade 3 endometrioid carcinomas were classified as type II tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations